Análise freireana do letramento em leitura do Programa Internacional de Avaliação de Estudantes (PISA) - Araujo, Enaide Severo de (2016)
It investigates the concept of literacy in reading of the Programme for International Student Assessment (PISA) coordinated by the Organization for Economic Cooperation and Development (OECD). PISA since its first edition in 2000, assesses, measures and provides indicators for global education systems. Researches claim PISA to be the beacon instrument of educational policies of member countries, which justifies the research in teaching area. It also presents evaluation concepts on a large scale in contrast to the assumptions of internal evaluation of school learning and provides analyzes of existing educational laws in Brazil related to the presence of subsidies given by PISA. Part of the following problem: what is the underlying concept of literacy to the Programfor International Student Assessment (PISA)? To perform the analysis, we assume that there are two models of literacy: autonomous and ideological (Street, 1999). It analyzes the following PISA official documents: Released Items in Reading 2009 (OECD, 2012), Reading Assessment Matrix (OECD, 2013) and Draft Reading Literacy Framework. (OECD, 2013b). It explicits, analyzes and criticizes the proposal for literacy assessment in PISA reading setting as analysis parameter the most emancipatory conception of reading of the Brazilian educator Paulo Freire (1921-1997). It concludes that PISA's test does not demand critical reading and historical knowledge, in a very different perspective of Paulo Freire's Model.